Addressing climate change adaptation and mitigation in tropical wetland ecosystems of Indonesia - Murdiyarso, Daniel; Kauffman, J.B. (Center for International Forestry Research, 2011)
Tropical wetlands, especially peatlands and mangroves, are important in global carbon cycling. Indonesia has more tropical wetlands than any other country on Earth. - Research that addresses critical information gaps and communicates the results on land use and carbon dynamics in tropical wetlands is needed to inform sound policy decisions. This work can also improve IPCC Guidelines on methodologies for greenhouse gas inventories. - Standardised methods and protocols are needed for effective monitoring, reporting and verification of emissions from land use and land cover change in tropical wetlands. - Low-lying coastal ecological zones are already affected by rising sea levels and other marine -related climate change effects. Mangroves are key to both climate change mitigation and adaptation. - Conservation and reducing degradation to tropical wetlands are both sound mitigation approaches and important adaptation strategies. Mitigation procedures that preserve ecosystem resistance and resilience to climate change are recommended as cost-effective and ecologically sound adaptation strategies. - Ecosystem-based or watershed-wide approaches provide the best lens through which communities can assess and manage with changing climate conditions.